O mexilhão Perna perna no Brasil: nativo ou exótico? - Pierri, B.; Fossari, T.; Magalhães, A. (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2016)
Mussel farming in Brazil is based on brown mussel Perna perna (Linnaeus, 1758), which is found throughout the Brazilian coast, especially abundant from Espírito Santo to Santa Catarina coast. In recent years it was suggested that Perna perna is an exotic species for the Brazilian coast. The hypothesis is based on the analysis of the zooarchaeology studies in archaeological sites in Brazil. All objections raised do not offer a conclusion, because they need specific studies with clear methodology, combining archeology, ecology and molecular biology. The aim of this work was to study the condition of the brown mussel Perna perna in Brazil if native or exotic, from survey results in archaeological sites, molecular techniques and dating of shells with C14. The dating indicated that the shells were 720±30 and 780±30 years, respectively. The calculation of divergence time indicated that the separation of the African and Brazilian mussel populations occurred around 200 thousand years ago. The results indicate the presence of the P. perna species in Brazilian territory long before the discovery of Brazil by the Portuguese in 1500, indicating that P. perna is actually a native species of Brazil.